Análise de sequências didáticas sobre o continente antártico a partir de aspectos ligados à astronomia no 8º ano da escola básica - Santos, Edson da Silva (2023)
The didactic phenomena linked to the learning of concepts associated with knowledge of climate dynamics and the four seasons in Antarctica may be linked to the poor performance of some students in understanding these concepts. One of the problems that leads to this situation, as far as their interpretative skills are concerned, is due to the practice and didactic choices made by teachers when teaching geography. One of the aims of this project was to provoke reflection on the problems of forming geographical concepts linked to astronomy in students, as well as on the training of 4th cycle elementary school teachers. In this research problem, the objective of understanding the change in the status of representations for definition, geometric theorems, hypotheses and conclusion, we pointed out the need to build teaching-learning situations that take into account the aspect of the importance of mobilizing the geometric figural and natural language representation registers in models for the understanding of geographical concepts, based on the methodology of Didactic Engineering and the Theory of Didactic Situations. The hypothesis that the activity of formulation is crucial to the acquisition of knowledge and problem solving in geometry and astronomy is linked to this apprehension, with the construction of didactic situations playing a crucial role in leading 8th grade students to a better understanding of the concepts involved in the acquisition of geometric skills. Considering the epistemological obstacles raised in the literature, we developed four didactic sequences with their respective educational products. In the results, the a posteriori analysis shows that the activities developed, during the didactic sequences, in a learning process through discussions and distinction between the definition and characteristics of the Antarctic region in association with the representation records, establishing the concept of climatic phenomena, which can lead to a definition of the season. The internal validation of the engineering was based on the articulation between the preliminary studies and the a priori analysis, with the findings made in the a posteriori analysis, partially present in this dissertation. In this analysis, difficulties were found related to the management of the activities developed and the processes of acquiring certain knowledge, especially those that require students to organize demonstration schemes and coordinate different registers of representation linked to the treatment of knowledge on the subject studied. These difficulties stem mainly from shortcomings in the institution's dominant didactic model in terms of the way the subject is presented in the textbook, and in the way, learning is assessed, which does not favor dissertative demonstrations.